Effect of Science and Technology Finance Policy on Urban Green Development in China - Gao, Chen; Song, Pingting; Wen, Ya; Yang, Deyong (Frontiers in Environmental Science, 2022)
Green sustainable development is a major challenge facing countries worldwide. Against the strategic background of innovation-driven development, studying the impact of science and technology finance policy (STFP) on urban green development is of great practical significance. Based on urban panel data from 2003 to 2019, this paper systematically examines whether and how STFP affects urban green development in China using the difference-in-differences (DID) method. The empirical results show that STFP has significantly stimulated the urban green development level, and the effect of policy implementation has increased first and then decreased over time. The findings remain robust when using propensity score matching-DID to avoid selection bias and other factors that may interfere with the estimation results. Additionally, technological innovation and green innovation are essential channels for STFP to improve urban green development. The impact of STFP is found to vary by region and by the level of urban innovation. Specifically, the policy effect is more pronounced in midwestern and high-innovation cities but less obvious in eastern and low-innovation cities. In conclusion, this paper provides city-level empirical evidence from China for an in-depth understanding of the green economy effect of STFP. It also provides theoretical guidance and policy references for accelerating the green transition in the context of sustainable development.